(untitled) (REVISTA DE HUMANIDADES Y CIENCIAS SOCIALES Y MULTIDISCIPLINARIA, 2021)
The translator plays a very important role within a global society. He/she enables the establishment of relations among people with different backgrounds and languages. When doing so, he/she is taking part in the cycle of communication, where the characters of author, translator and reader are interchangeable. The aim of this article is to discuss the role of the translator in the society as well as to describe and analyse the expert knowledge he has to acquire in order to perform a good job.